Mental Health Nursing: Pengaruh Edukasi Dengan Media Video Terhadap Kedaruratan Self Harm Pada Remaja Di Kabupaten Ponorogo - Sukamto, Filia Icha; Nasriati, Ririn; Munawaroh, Siti; Dwi Rahayu, Yayuk (Nursing Sciences Journal, 2024)
Self Harm is a behavior that tends to harm oneself to overcome the pain experienced emotionally due to psychological problems and pressures that can lead to suicide and can cause death. Adolescents tend to do self harm as an effort to overcome various emotional pressures they experience. The purpose of this study was to determine the effect of education with video media on self-harm behavior in adolescents. The design of this study used pre-experimental research, one group pretest and post-test. The sample of this study was adolescents in Koripan Village, Bungkal District, Ponorogo with a total of 43 people taken using purposive sampling techniques. Data analysis used the Wilcoxon Sign Rank test. The results of the statistical test obtained a significance value (p value = 0.340 <a = 0.05, so it can be concluded that there is no effect of education with videos on self-harm behavior in adolescents. The results of this study indicate that to change self-harm behavior in adolescents is not effective enough to use educational videos alone but requires other interventions.